KUALITAS PENCAHAYAAN ALAMI DAN KENYAMANAN VISUAL RUANG KELAS DI KAMPUS ITSB - Adhi Risnandar, Firman Fadhly (JOURNAL OF APPLIED SCIENCE (JAPPS), 2024)
Visual comfort in classroom is very important to support the teaching and learning process. The use of natural lighting is important in relation to energy conservation issues. ITSB Campus building has a fairly wide opening design, which is also one of the factors that has been met, in relation to the green certification that has been obtained by ITSB Campus. However, these wide openings have not been utilized optimally. Most students and lecturers still use lamps during the day in the teaching and learning process. The purpose of this study was to measure the contribution and quality of natural lighting in classrooms at ITSB Campus to visual comfort in the teaching and learning process. Measurement of the intensity of natural lighting was carried out using a light meter, while the level of visual comfort was carried out by filling out a questionnaire. Evaluation of natural lighting was reviewed based on the distribution of lighting entering classroom which refers to classroom lighting standards. Meanwhile, the level of visual comfort was reviewed based on the level of student satisfaction to the quality of lighting that was simulated directly in classroom